A case study on the organizational innovations and challenges of a comprehensive school providing extensive bilingual education - Pekkarinen, Erkka (2019)
The goal of this case study was to document the challenges and innovative practices of a large Finnish comprehensive school organization providing an extensive bilingual education program. The study was conducted in 2018. This qualitative single-case study was conducted through a weeklong period of data collection. Data was collected through participant-observation, semi-structured thematic interviews and an ethnographic research diary. The participants of the study consisted of sixteen stakeholders acting in different positions within the same school organization, all of which were somehow involved in the implementation of the extensive bilingual education program. After analyzing the data through thematic analysis, four reciprocally interactive challenge-innovation pairs were found to shape the dynamics of the organization. These pairs were rigidness/flexibility, alienation/unity, indifference/investment and solitude/collaboration. In addition to the pairs being mutually reciprocal, the findings suggest that a causal relationship exists between each of the challenges and innovations, in which the innovations result from the challenges. Five key mechanisms (collaboration, self-efficacy, collective efficacy, collective investment and time) were identified as parts of this causal process. The findings were further supported by commonalities found in existing research on the fields of educational leadership and bilingual education. The process of transformation from challenges to innovations documented in this study has implications for developing effective organizational practices for implementing bilingual education programs in schools across different contexts.